Activating EGFR Signaling Attenuates Osteoarthritis Development Following Loading Injury in Mice. (17th October 2022) - Gui, Tao; Wei, Yulong; Luo, Lijun; Li, Jun; Zhong, Leilei; Yao, Lutian; Beier, Frank; Nelson, Charles L.; Tsourkas, Andrew; Liu, X. Sherry; Enomoto‐Iwamoto, Motomi; Yu, Feifan; et al.
ABSTRACT: Posttraumatic osteoarthritis (PTOA) results in joint pain, loss of joint function, and impaired quality of daily life in patients with limited treatment options. We previously demonstrated that epidermal growth factor receptor (EGFR) signaling is essential for maintaining chondroprogenitors during articular cartilage development and homeostasis. Here, we used a nonsurgical, loading‐induced PTOA mouse model to investigate the protective action of EGFR signaling. A single bout of cyclic tibial loading at a peak force of 6 N injured cartilage at the posterior aspect of lateral femoral condyle. Similar loading at a peak force of 9 N ruptured the anterior cruciate ligament, causing additional cartilage damage at the medial compartment and ectopic cartilage formation in meniscus and synovium. Constitutively overexpression of an EGFR ligand, heparin binding EGF‐like growth factor (HBEGF), in chondrocytes significantly reduced cartilage injury length, synovitis, and pain after 6 N loading and mitigated medial side cartilage damage and ectopic cartilage formation after 9 N loading. Mechanistically, overactivation of EGFR signaling protected chondrocytes from loading‐induced apoptosis and loss of proliferative ability and lubricant synthesis. Overexpressing HBEGF in adult cartilage starting right before 6 N loading had similar beneficial effects. In contrast, inactivating EGFR in adult cartilage led to accelerated PTOA progression with elevated cartilage Mankin score and synovitis score and increased ectopic cartilage formation. As a therapeutic approach, we constructed a nanoparticle conjugated with the EGFR ligand TGFα. Intra‐articular injections of this nanoconstruct once every 3 weeks for 12 weeks partially mitigated PTOA symptoms in cartilage and synovium after 6 N loading. Our findings demonstrate the anabolic actions of EGFR signaling in maintaining articular cartilage during PTOA development and shed light on developing a novel nanomedicine for PTOA. © 2022 American Society for Bone and Mineral Research (ASBMR).